Positronium laser cooling in a magnetic field - Zimmer, Christian; Yzombard, Pauline; Camper, Antoine; Comparat, Daniel (Physical review, 2021)
We study realistic 3D laser cooling of positronium (Ps) in the presence of a magnetic field. Triplet and singlet states mixing due to the magnetic field, and dynamical Stark effect, generally produce higher annihilation rates than in the zero-field case. 3D cooling is efficient only at very low field B less than or similar to 50 mT and at high field values B greater than or similar to 0.7 T. Near 100 ns long laser pulses, spectrally broad enough to cover most of the Ps Doppler profile and with energy in the mJ range, are required to cool Ps. Simulations based on full diagonalization of the Stark and Zeeman Hamiltonian and a kinetic Monte Carlo algorithm exactly solving the rate equations indicate that an efficient cooling (typically from 300 K down to below 50 K) is possible even in a magnetic field. We also propose 3D moving molasses cooling that can produce a well-defined monochromatic Ps beam useful for applications.
Gesehen am 20.01.2022